Концепція права Герберта Харта - Дудченко, Валентина Віталіївна; Дудченко, Валентина Витальевна; Dudchenko, V. (My University, 2012)
Such components of law, as methodology, criticism of the imperative theory of law, researches of law as the union of primary and secondary rules, justice and morality, natural law and legal positivism, the legal validity and moral value are analysed. All components of the concept are united depend from combining and revision of concepts such as legislation, jurisdiction, legal validity, sources of law, legal sanction, the state, authority, offi cial.
Дудченко В. В. Концепція права Герберта Харта / В. В. Дудченко // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України ; НУ ОЮА. – Одеса : Фенікс, 2012. – Вип.. 46. – С. 9-18.
Keywords: теорія права; методологія права; критика імперативної теорії права; переосмислення основних правових понять; теория права; методология права; критика императивной теории права; переосмысление основных правовых понятий; legal theory; methodology rights; Hrithik's imperative theory of law; rethinking the basic legal concepts